POTENSI CHITOSAN DAN ESSENTIAL OIL BAWANG PUTIH (Allium sativum) YANG DIINKORPORASIKAN PADA EDIBLE COATING SEBAGAI PENGAWET BAKSO - Setyaningrum Ariviani; Miladyah Kusumawati (AGROINTEK, 2021)
Beef Meatball is a processed meat product that is susceptible to microbiological damage, thus requiring preservatives to extend their shelf life. Natural preservatives incorporated into edible coatings are more effective than those added directly to the food. This study aims to investigate the potential of chitosan and garlic (Allium sativum) essential oil (EO) incorporated into edible coatings as a natural preservative alternative of beef meatballs. Beef meatballs were coated with 4 variations of edible coatings, namely without incorporation (control), with the incorporation of chitosan, garlic EO, and chitosan-garlic EO. These coated beef meatballs were stored at 4 ± 10 0C and further analyzed for the evaluation of total microbe level (Total Plate Count) and texture measurement in the storage period of 0, 5, 10, 14, and 18 days. The potential of chitosan and EO of garlic as an antimicrobial agent was determined by MIC (Minimum Inhibitory Concentration) analysis of E.coli. The results showed that the chemical characteristics of beef meatballs which include the levels of moisture, ash, fat, and protein met to the National Standard of Indonesia (SNI). Garlic EO has a lower MIC value than chitosan, so the garlic EO incorporated in the edible coating is more effective as a preservative of meatballs than chitosan. The chitosan-garlic EO incorporation in edible coating provides an antagonistic effect in inhibiting the microbial growth of beef meatballs during storage. All treatments showed not significantly different on the rate of texture change of the beef meatballs during storage, although the differences in the total microbial levels were observed. The research results have important consequences in the use of natural preservatives to extend the shelf life of beef meatballs through incorporation into edible coatings.